DIGITAL METASTATIZING MALIGNANT MELANOMA IN A DOE - Sutharia, Prajwalita (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Reportedly, melanomas of goats are highly malignant, especially those arising on the digits and on mucocutaneous junctions are locally aggressive, and commonly metastasize to other organs via the lymphatics and the blood stream (Valentine, 2004; Smith et al., 2002;). In present case hard increasing swelling in region of prescapular lympnodes was noticed, FNAC examination of which revealed metastasis characterized by heavily dark black to green colour pigmented cells obscuring cellular and nuclear detail. Common sites for metastasis include regional lymph nodes, lungs, and liver, (Aydogan et al., 2013). Surgical excision, the oldest method in the fight against cancer, is still considered the treatment of choice (Mavangira et al., 2008) but looking towards the extensive spread of tumor amputation of affected digit was performed under regional nerve block after application of a tourniquet which minimized intra-operative haemorrhage. The doe made an uneventful recovery with normal ambulation on all four limbs even though the prognosis of malignant melanomas in goats is considered guarded to poor (Ramadan et al., 1988) or grave (Smith et al., 2002).